A genome-wide resource for the analysis of protein localisation in Drosophila - Mihail Sarov; Christiane Barz; Helena Jambor; Marco Y Hein; Christopher Schmied; Dana Suchold; Bettina Stender; Stephan Janosch; Vinay Vikas KJ; RT Krishnan; Aishwarya Krishnamoorthy; Irene RS Ferreira; et al. (eLife, 2016)
The Drosophila genome contains >13000 protein-coding genes, the majority of which remain poorly investigated. Important reasons include the lack of antibodies or reporter constructs to visualise these proteins. Here, we present a genome-wide fosmid library of 10000 GFP-tagged clones, comprising tagged genes and most of their regulatory information. For 880 tagged proteins, we created transgenic lines, and for a total of 207 lines, we assessed protein expression and localisation in ovaries, embryos, pupae or adults by stainings and live imaging approaches. Importantly, we visualised many proteins at endogenous expression levels and found a large fraction of them localising to subcellular compartments. By applying genetic complementation tests, we estimate that about two-thirds of the tagged proteins are functional. Moreover, these tagged proteins enable interaction proteomics from developing pupae and adult flies. Taken together, this resource will boost systematic analysis of protein expression and localisation in various cellular and developmental contexts.